The Intersection of AI Advancements in Judicial Systems and Media Trials - Ramadhani, Evyta (Indonesian Journal of Law and Society, 2024)
In the ever-evolving landscape of jurisprudence, the integration of technology, particularly Artificial Intelligence (AI), has become increasingly prevalent, reshaping the dynamics of judicial proceedings and legal discourse worldwide. Concurrently, the phenomenon of "media trials" has gained momentum, particularly in countries like the United States and the United Kingdom, where media influence often intersects with legal processes. When talking about technological advancements, especially in the context of Artificial Intelligence, we often get caught up in thinking that technology is a neutral and objective entity. Advancements in AI have revolutionized various aspects of judicial systems, promising efficiency, accuracy, and accessibility. From case management to legal research and predictive analytics, AI-powered tools have emerged as indispensable assets for legal professionals. In adjudication, AI algorithms are increasingly utilized for tasks such as document analysis, evidence evaluation, and even judicial decision-making in some contexts.